2016
DOI: 10.1016/j.scriptamat.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state dewetting and island morphologies in strongly anisotropic materials

Abstract: We propose a sharp-interface continuum model based on a thermodynamic variational approach to investigate the strong anisotropic effect on solid-state dewetting including contact line dynamics. For sufficiently strong surface energy anisotropy, we show that multiple equilibrium shapes may appear that can not be described by the widely employed Winterbottom construction, i.e., the modified Wulff construction for an island on a substrate. We repair the Winterbottom construction to include multiple equilibrium sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 40 publications
3
77
0
Order By: Relevance
“…These earlier studies were focused on the isotropic surface energy, although recent experiments have demonstrated that the crystalline anisotropy could play important roles in solid-state dewetting. To include the surface energy anisotropy, many approaches have been proposed in recent years, such as a discrete model [13], a kinetic Monte Carlo model [42,15], a crystalline model [9,65] and continuum models based on partial differential equations [5,25,26,55]. From a mathematical perspective, theoretical solid-state dewetting studies can be categorized into two major problems: one focuses on the equilibrium of solid particles on substrates [4,33]; the other focuses on investigating the kinetic evolution of solid-state dewetting [25,26,55].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These earlier studies were focused on the isotropic surface energy, although recent experiments have demonstrated that the crystalline anisotropy could play important roles in solid-state dewetting. To include the surface energy anisotropy, many approaches have been proposed in recent years, such as a discrete model [13], a kinetic Monte Carlo model [42,15], a crystalline model [9,65] and continuum models based on partial differential equations [5,25,26,55]. From a mathematical perspective, theoretical solid-state dewetting studies can be categorized into two major problems: one focuses on the equilibrium of solid particles on substrates [4,33]; the other focuses on investigating the kinetic evolution of solid-state dewetting [25,26,55].…”
mentioning
confidence: 99%
“…The above governing equation is well-posed when the surface energy is isotropic or weakly anisotropic. But when the surface energy is strongly anisotropic, some missing orientations will appear on equilibrium shapes [47,50]; in this case, the governing equation becomes ill-posed, and it can be regularized by adding regularization terms such that the regularized sharp-interface model is well-posed [25,5]. For the analytical criteria about the classification of surface energy anisotropy in 3D, interested readers could refer to [47].…”
mentioning
confidence: 99%
“…In order to understand this condition, we may consider two limiting cases as η = 0 and η = ∞: (i) when η = 0, the contact line moving velocity is zero, and we prescribe a fixed boundary condition such that the contact line does not move; and (ii) when η → ∞, as we always assume that the moving velocity should be finite, condition (ii) will reduce to the so-called anisotropic Young equation [30,4] (2.10) c γ Γ · n Γ − σ = 0. which prescribes an equilibrium contact angle condition. Therefore, condition (ii) actually allows a relaxation process for the dynamic contact angle evolving to its equilibrium contact angle [49,28]. The last condition (iii) ensures that the total volume/mass of the thin film is conserved during the evolution, i.e., no-mass flux at the moving contact line.…”
Section: Substratementioning
confidence: 99%
“…Solid-state dewetting of thin films belongs to the evolution of an open curve/ surface governed by surface diffusion and contact line migration [27,49,28,5,30]. In earlier years, the marker-particle method was firstly presented for solving sharpinterface models of solid-state dewetting in two dimensions (2D) [51,49] and three dimensions (3D) [18].…”
mentioning
confidence: 99%
“…Moreover, the phase field approaches for solid-state dewetting have also been proposed for both isotropic [20,21] and anisotropic surface energy [22], which can naturally capture the complex topology change during the evolution. More recently, the two-dimensional solid-state dewetting has been fully studied via sharp interface models [23][24][25][26]. In these models, the interface between the thin film and vapor is assumed to be an open curve with two endpoints (the contact points) attached on the x axis (flat substrate).…”
Section: Introductionmentioning
confidence: 99%